A generic graphical approach for simultaneous targeting and design of a gas network - Wan Alwi, Sharifah Rafidah (Elsevier B.V., 2009)
This paper presents a generic graphical approach for simultaneous targeting and design of a utility gas network. The approach has been effectively and interactively used to target the minimum utility gas flow rate and design a maximum nitrogen gas recovery network. A graphical tool known as Network Allocation Diagram (NAD) is introduced to assist designers to graphically visualize, explore, evolve, and systematically select networks that yield either the minimum gas targets or the minimum number of streams. Application of this approach results in a potential reduction of 33.8% fresh gas and waste gas.